Benefit-Cost Analysis of Apiculture Enterprise: A Case Study of Jutpani VDC, Chitwan, Nepal - Devkota, KH (Journal of the Institute of Agriculture and Animal Science, 2006)
A survey study was conducted to study the benefit-cost analysis of apiculture enterprise in Jutpani VDC, Chitwan district. Data were collected by interviewing randomly selected 18 beekeepers for sample survey. Benefit : Cost (BC) ratio of apiculture was computed by including and excluding the revenue obtained from colony selling. Only 61.11% of beekeepers sold bee colonies for earning income. The study revealed that BC ratios of apiculture were 2.41 and 1.58 in the case of inclusion and exclusion of the income received from the colony selling, respectively. It showed that apiculture industry was running in profit in both cases. In the former case, the BC ratio ranged from 0.97 to 6.22 and about 88.88% beekeepers were in profit. The BC ratio in the later case ranged from 0.43 to 3.41 and about 77.77% beekeepers were in profit. The number of colonies ranged from 2 to 54 with an average of 21.33 colonies per bee farm. In the former case, average annual income was Rs. 70758.33 (US$ 969.29 approximately) per farm and Rs. 49588.31 (US$ 679.29 approximately) in the later case. Likewise, the average income per colony per annum was Rs. 3317.31 (US$ 45.44) and Rs. 1777.65 (US$ 24.35 approximately) in the former and later case, respectively. Key words : Apiculture, benefit-cost ratio, beekeeperJ. Inst. Agric. Anim. Sci. 27:119-125 (2006)